If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8v + -21 = 2v + -9 Reorder the terms: -21 + 8v = 2v + -9 Reorder the terms: -21 + 8v = -9 + 2v Solving -21 + 8v = -9 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. -21 + 8v + -2v = -9 + 2v + -2v Combine like terms: 8v + -2v = 6v -21 + 6v = -9 + 2v + -2v Combine like terms: 2v + -2v = 0 -21 + 6v = -9 + 0 -21 + 6v = -9 Add '21' to each side of the equation. -21 + 21 + 6v = -9 + 21 Combine like terms: -21 + 21 = 0 0 + 6v = -9 + 21 6v = -9 + 21 Combine like terms: -9 + 21 = 12 6v = 12 Divide each side by '6'. v = 2 Simplifying v = 2
| 18w-5w+29=6w-27 | | 2v+5=4v+13 | | 15x^2=2x-1 | | 1=2x/x-2 | | 2n^2+3x-5=0 | | 6+(-2)= | | 2y^2+5y+2=8+4y | | 11p-7=2p+1 | | 6x=12+2x | | (-5)(-3)(-2)-(-3)= | | 7.6+(-8.2)= | | 3+2m-1=6m+12-2m | | -2=3x^2+5x | | 18a+18b= | | x(2x-3)=6 | | x-18=23 | | 10-18+3x=2x | | 3*x^2-16*x+15=0 | | -7.7x=61.6 | | x^2+5*x-7=0 | | 5x-x=-39 | | 6(x+2)-(2x-7)= | | 6y+4-2y=1+3y-7 | | x(28-x)=192 | | (8x+5)-(6x-7)= | | -4(4b+4)+(17b-3)=0 | | -90z-0.9=-100z+1.5 | | 90z-0.9=-100z+1.5 | | -7(5y+7)= | | 2.1q-5.2-3.5q=-2.4q-4.1 | | x^3-5x^2-11x-3=0 | | 4m+8=-8 |